Granulate Ambrosia Beetle, Xylosandrus crassiusculus (Motschulsky) (Insecta: Coleoptera: Curculionidae: Scolytinae) - Thomas H. Atkinson; John L. Foltz; Robert C. Wilkinson; Russell F. Mizell (EDIS)
The granulate ambrosia beetle is a minute ambrosia beetle of Asian origin that was first detected near Charleston, South Carolina. It can become abundant in urban, agricultural, and forested areas and has been reported as a pest of nursery stock and young trees in the Old World tropics and of peach trees in South Carolina. It is a potentially serious pest of ornamentals and fruit trees and is reported to be able to infest most trees and some shrubs (azalea), except for conifers. Learn more in this revised 4-page fact sheet was written by Thomas. H. Atkinson, John L. Foltz, Robert C. Wilkinson, and Russell F. Mizell and published by the UF Department of Entomology and Nematology, March 2011.